Mitigation of the Impact of Abrasion Pasir Panjang Beach in Singkawang City - Wulandari, Fajar; Khoirunisa, Nanda; Soeharto, Soeharto (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
This research studies aim to mitigate the community against the impact of abrasion disasters in the Pasir Panjang area of ​​Singkawang City. This research is qualitative research, which is a research procedure that produces descriptive data in the form of words, images, and not numbers, from people or observable behaviour. Sourcing from this research uses purposive sampling, which is sampling based on research options on mitigating the impact of abrasion and experiencing communities living in the area of Pasir Panjang beach. Impact of abrasion in Pasir Panjang Beach, South Singkawang is caused by natural and human factors. Natural factors that cause abrasion are erosion of the beach by the flow of seawater that is a meander, wind waves (waves) and rising seawater. Whereas the human factor that contributes to abrasion is the taking of coastal materials such as sea sand, coral reefs, and mining. The impact of coastal abrasion eventually worsened the situation so that the existing bridge was broken because of the strong waves of Pasir Panjang Beach.